Projeto canhão : o ensino de funções quadráticas com o auxílio do software GeoGebra - Cance, Cesar Augusto (Universidade Federal de São Carlos, 2015)
This work presents the development and implementation of a didactic sequence in order to motivate and teach school students quadratic functions. To do this, we built a cannon made of tiner cans and prepared a serie of activities that have been subdivided into three phases: construction, competition and activities with the use of the software GeoGebra. The work done with students in these aroused a greater interest in the matter and was extremely valuable because students did not forget the acquired learning.
Keywords: Função quadrática; Gráfico de função quadrática; Atividades no GeoGebra; Quadratic function; Graph of a quadratic function; Activities in GeoGebra; CIENCIAS EXATAS E DA TERRA::MATEMATICA::GEOMETRIA E TOPOLOGIA::GEOMETRIA DIFERENCIAL; CIENCIAS EXATAS E DA TERRA::MATEMATICA::ALGEBRA